(untitled) (Jurnal Sustainable, 2024)
The research method used is qualitative with a descriptive approach which is a study to determine facts with appropriate interpretation to recognize phenomena that accurately describe the characteristics of the phenomena that are occurring. The research results show that higher education administration has a significant role in facilitating effective supervision practices by coordinating communication between higher education management, lecturers and support staff, providing necessary resources, and facilitating training and professional development for supervisors. It is hoped that this research will provide insight for educational practitioners and other related parties regarding the importance of the role of administration and supervision in higher education environments in improving the quality of education through effective administration and supervision practices. This research aims to investigate the role of campus administration in encouraging effective supervision practices. Data was collected through in-depth interviews with campus administration staff, supervisors, lecturers and leaders at Pertiba University. The research results show that the Pertiba University campus administration has a significant role in facilitating and coordinating effective supervision practices. Factors such as good communication, accurate data management, and a deep understanding of the needs of higher education institutions are key in creating an environment conducive to effective supervision practices.